Gibbs-Curie-Wulff Theorem in Organic Materials A Case Study on the Relationship between Surface Energy and Crystal Growth - Li, Rongjin (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.